Numerical simulation of wave interacting with a submarine outfall using IH-2VOF - Inverno, J. (2013)
IH-2VOF numerical model is applied to study wave interacting with a circular cylinder with a diameter of 0.02 m in a water depth of 0.27 m, with a wave period of 1.08 s and a wave height of 0.047 m. The study includes analyses of convergence with the mesh discretization. The convergence of forces, velocities and Keulengan-Carpenter number was obtained when 32 cells were used to define the cylinder. The influence of the wall proximity on the forces was also analyzed and 15 different ratios between the pipe distance from the bottom and the pipe diameter were simulated, varying from 0.0625 to 1.5. Results of lift, drag and inertia coefficients are compared with the experimental results of the experimental study of Jarno-Druaux et al. (1995) and the same trend in the variation with the gap between the cylinder and the bottom was obtained with the model giving slightly larger values.